2017
DOI: 10.1103/physrevaccelbeams.20.033201
|View full text |Cite
|
Sign up to set email alerts
|

Development and operation of a Pr2Fe14B based cryogenic permanent magnet undulator for a high spatial resolution x-ray beam line

Abstract: Short period, high field undulators are used to produce hard X-rays on synchrotron radiation based storage ring facilities of intermediate energy and enable short wavelength Free Electron Laser. Cryogenic permanent magnet undulators take benefit from improved magnetic properties of RE2F e14B (Rare Earth based magnets) at low temperatures for achieving short period, high magnetic field and high coercivity. Using P r2F e14B instead of N d2F e14B, which is generally employed for undulators, avoids the limitation … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(15 citation statements)
references
References 35 publications
0
15
0
Order By: Relevance
“…We choose a set of parameters (see table 1) compatible with the most recent achievements of the groups targeting both quality and reliability, mandatory for an FEL application [21,42,[44][45][46]. With a short period undulator [47], these typical 200 MeV beams can be used to target the vacuum ultra-violet range. We therefore consider a seed at 160 nm (see table 1) generated in gas [48,49] using a branch of the main laser [49].…”
Section: Methodsmentioning
confidence: 99%
“…We choose a set of parameters (see table 1) compatible with the most recent achievements of the groups targeting both quality and reliability, mandatory for an FEL application [21,42,[44][45][46]. With a short period undulator [47], these typical 200 MeV beams can be used to target the vacuum ultra-violet range. We therefore consider a seed at 160 nm (see table 1) generated in gas [48,49] using a branch of the main laser [49].…”
Section: Methodsmentioning
confidence: 99%
“…As will be discussed in the section "Comparison of Generic CPMU Model Calculations to Real Undulators" the magnet heights chosen for the CPMUs that have been built (and for which magnet dimensions were published) are indeed shorter. The pole is assumed to be 0.8 cm shorter than the magnet; this is close to the values found in thoroughly optimized APS models with taller magnets, and it is also the value chosen for the CPMU at SOLEIL [9]. The difference in B eff between a magnet height of 3 cm and 5 cm is about 1% (see Fig.…”
Section: Computed Magnetic Fields Of Cryogenic Permanent Magnet Undulmentioning
confidence: 74%
“…(The spin reorientation reduces the on-axis undulator field if magnets are cooled below the transition temperature.) As a result, many recent undulators are constructed with PrFeB magnets [9]. This study presents results for both magnet materials.…”
Section: Introductionmentioning
confidence: 98%
“…The magnetic characteristics of several magnet materials were explored at SPring-8 [22], SOLEIL [25] and HZB [26,27] to characterize the magnetic performance of CPMUs. At ESRF in 2008, a 2-m long CPMU with a period length of 18 mm was built based on NdFeB magnets [28] becoming the first full-scale CPMU operating in a storage ring [29,30] followed by other CPMUs operating in storage rings such as SOLEIL [31], DLS [32], SLS [33] and ESRF [34]. A CPMU at ESRF demonstrated that a nonbaked device can operate smoothly in a storage ring [34].…”
Section: Introductionmentioning
confidence: 99%
“…A CPMU at ESRF demonstrated that a nonbaked device can operate smoothly in a storage ring [34]. The first full-scale PrFeB-CPMU with a period length of 18 mm has been designed and operated in the storage ring at SOLEIL [31]. From then on, PrFeB-CPMUs have become the preferred choice for the development of CPMUs because of the higher magnetic field compared to NdFeB-CPMUs.…”
Section: Introductionmentioning
confidence: 99%